Seleção de fêmeas de Pseudopimelodus mangurus, Pimelodus maculatus e Prochilodus lineatus aptas à reprodução através da ultrassonografia - Arashiro, Dilberto Ribeiro (2021)
The aim of this study was to stablish a methodology to female able to spawn selection and sexing by ultrasonography for the neotropical catfishes Pseudopimelodus mangurus and Pimelodus maculatus. Fish were anesthetized and then measured for its weight, length, height, width of the body giving rise to biometric data: 1.061 ± 0.452 kg, 34.886 ± 5.291 cm, 7.257 ± 1560 cm, 8.586 ± 2.34 cm respectively for P. mangurus who spawn and 482.500 ± 118.366 g, 28.329 ± 2.426 cm, 7.626 ± 0.972 cm and 5.261 ± 0.756 cm respectively for P. maculatus who spawn. Ultrasonography was made in ventral region of the animals measuring ovary height, ovary width and ovary area, giving rise to biometric data: 2.763 ± 0.793 cm, 2.693 ± 0.477 cm and 14.867 ± 6.873 cm2 respectively for P. mangurus who spawn and 2.576 ± 0.583 cm, 1.917 ± 0.374 and 8.738 ± 2.824 cm2 for P. maculatus who spawn. After ultrasonography, fish of both species were induced to spawn, being seventeen females of P. mangurus and forty-two P. maculatus, were only seven P. mangurus and thirty-four P. maculatus spawned, giving rise to the following reproductive: data: relative oocytes weight (117.373 ± 62.272 g), number of oocytes per gram (645 ± 80.060), total fecundity (67.770 ± 30.271), fertilization rate (90,58 ± 15,90%), and hatching rate (72,07 ± 31,09%) for P. mangurus and relative oocytes weight (47.517 ± 25.256 g), number of oocytes per gram (3.415 ± 3.415), total fecundity (79.082 ± 57.622%), fertilization rate (76,47 ± 22,31%), and hatching rate (39 ± 30,67%) for P. maculatus. For both species the ultrasound presented a highly accuracy for sexing at the reproductive season and can be applied in reproductive studies as a non-invasive technique replacing invasive methods that can compromise de reproductive success.